PANDANGAN SOSIAL TERHADAP STRES DAN TRAUMA SETELAH BENCANA (Studi Kasus pada Masyarakat Aceh Pascabencana Gempa dan Tsunami Tahun 2004) - Syahputra, Andi (Universitas Muhammadiyah Aceh, 2012)
An individual or a communities that impact disaster will begin their new life, its mean to differ from condition likes before disaster was happened. This change is one of the condition which susceptible towards appearance many pressures in life to every human. Following the guidebook